Pelestarian Budaya Lokal dan Peran Esensial Generasi Z dalam Ekowisata Berkelanjutan di Kampung Caping - Aryasa, Hence Made; Fenisa , Delta; Linanda, Pratika; Sumaryanti, Atin; Putri, Atika Wulandari (Universitas Dinamika, 2025)
This activity aims to empower the local community through the development of sustainable ecotourism in Wisata Caping village, Pontianak Tenggara. The Kapuas River's waterfront area holds significant potential, offering natural beauty and rich local culture, yet it faces challenges related to low environmental conservation awareness. The activity engaged 24 participants, primarily Generation Z, who acted as change agents by leveraging technology to support this initiative. The methods employed included planning, workshops, field practices, as well as evaluation and monitoring. Training focused on waste bank management, the creation of cultural-based local products, and the promotion of ecotourism through digital media. This initiative also fostered collaboration among community members, volunteers, and academics. The implications of this activity encompass increased environmental awareness, reduced waste pollution, and economic growth through ecotourism. Generation Z played a vital role in disseminating information and engaging the community, creating a replicable model of sustainable tourism management. The program successfully enhanced community skills while balancing environmental conservation with economic welfare. Regular monitoring and evaluation ensure that the program continues to generate positive impacts for Kampung Wisata Caping and its surrounding areas.